Answer:
the solution is (2, -6)
Step-by-step explanation:
Substitute the second equation into the first, replacing y in the first:
2x - (-4x+2) = 10
Simplifying, we get:
2x + 4x - 2 = 10, or:
6x = 12, which yields x = 2.
Substituting 2 for x in the second equation yields y = -4(2) + 2 = 0, or y = -6
Then the solution is (2, -6).
Answer:
the answer is 58 your welcome
X>-6 is what i believe the answer is.
hope this helps!
Answer: Option d.
Step-by-step explanation:
The trigonometric identity needed is:
![csc^2\theta=cot^2\theta+1](https://tex.z-dn.net/?f=csc%5E2%5Ctheta%3Dcot%5E2%5Ctheta%2B1)
Knowing that
:
Substitute it into
:
![csc^2\theta=(\frac{4}{3})^2+1](https://tex.z-dn.net/?f=csc%5E2%5Ctheta%3D%28%5Cfrac%7B4%7D%7B3%7D%29%5E2%2B1)
Simplify the expression:
![csc^2\theta=(\frac{4}{3})^2+1\\\\csc^2\theta=\frac{16}{9}+1\\\\csc^2\theta=\frac{25}{9}](https://tex.z-dn.net/?f=csc%5E2%5Ctheta%3D%28%5Cfrac%7B4%7D%7B3%7D%29%5E2%2B1%5C%5C%5C%5Ccsc%5E2%5Ctheta%3D%5Cfrac%7B16%7D%7B9%7D%2B1%5C%5C%5C%5Ccsc%5E2%5Ctheta%3D%5Cfrac%7B25%7D%7B9%7D)
Solve for
. Apply square root at both sides of the expression:
![\sqrt{csc^2\theta}=\±\sqrt{\frac{25}{9}}](https://tex.z-dn.net/?f=%5Csqrt%7Bcsc%5E2%5Ctheta%7D%3D%5C%C2%B1%5Csqrt%7B%5Cfrac%7B25%7D%7B9%7D%7D)
![csc\theta=\frac{5}{3}](https://tex.z-dn.net/?f=csc%5Ctheta%3D%5Cfrac%7B5%7D%7B3%7D)